2023
DOI: 10.3390/antibiotics12040749
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanisms of Carbapenem Resistance in Klebsiella pneumoniae: A Study on IS26 Integrons, Beta-Lactamases, Porin Modifications, and Plasmidome Analysis

Abstract: The emergence of carbapenem-resistant Klebsiella pneumoniae poses a significant threat to public health. In this study, we aimed to investigate the distribution and genetic diversity of plasmids carrying beta-lactamase resistance determinants in a collection of carbapenem-resistant K. pneumoniae blood isolates. Blood isolates of carbapenem-resistant K. pneumoniae bacteremia were collected and identified. Whole-genome sequencing, assembly and analysis were performed for the prediction of antimicrobial resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Out of the total 50 isolates of K. pneumoniae, 24 isolates were analyzed by WGS, including the 7 isolates which were successful in conjugation. Sixteen of these isolates were positive for the variable regions ( Kp 5,7,10,11,15,16,21,28,37,40,42,43,44,45,46,and 49) and two isolates showed bands with an unexpected size for the intI3 gene (Kp 4 and Kp 22). According to previous studies, these bands could be variants of integrase genes [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the total 50 isolates of K. pneumoniae, 24 isolates were analyzed by WGS, including the 7 isolates which were successful in conjugation. Sixteen of these isolates were positive for the variable regions ( Kp 5,7,10,11,15,16,21,28,37,40,42,43,44,45,46,and 49) and two isolates showed bands with an unexpected size for the intI3 gene (Kp 4 and Kp 22). According to previous studies, these bands could be variants of integrase genes [35].…”
Section: Resultsmentioning
confidence: 99%
“…Integrons, for example, are semi-mobile platforms that recognize and capture mobile gene cassettes and transform them to usable genes by ensuring their appropriate expression [8][9][10]. They are located on different MGEs, such as plasmids, transposons, and pathogenicity islands (PAIs), which enable their movement between different bacteria [11,12]. A number of studies showed that most K. pneumoniae clinical isolates carried class 1 integrons, whereas class 2 integrons were only present in 1-2% of the isolates and rarely harbored class 3 integron [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenem resistance, however, does not only depend on the presence of carbapenemases genes but may also be conferred by the combination of alternative mechanisms, such as the action of ESBL or AmpC enzymes, together with decreased membrane permeability and/or the over-expression of efflux pumps ( Goessens et al, 2013 ; Guerra et al, 2014 ; van Boxtel et al, 2016 ; Tseng et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%